The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1182/blood.v76.1.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Surface-dependent reactions of the vitamin K-dependent enzyme complexes

Abstract: During the past 20 years contributions from many laboratories have led to the development of isolation procedures, delineation of primary structures, and more recently, to the expression of recombinant proteins associated with the coagulation cascade. In general, studies of coagulation proteins under defined conditions have demonstrated the prescience of Davie and Ratnoff and MacFarlane in their proposals of the coagulation cascade. The more recent discovery of thrombomodulin by Esmon et al has led to the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
423
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 872 publications
(434 citation statements)
references
References 2 publications
8
423
0
3
Order By: Relevance
“…The activated enzyme (factor Xa) is an Arg-specific serine protease related to trypsin, but has much narrower substrate specificity. The N-terminal γ-carboxyglutamic acid (Gla) domain binds B8À10 calcium ions in a cooperative manner (average K d B 0.5 mM) and mediates the interaction of factor X/Xa with phospholipid membranes [4,5,6]. In the presence of calcium ions, factor Xa forms a phospholipid-bound complex with a cofactor, factor Va.…”
Section: Activity and Specificitymentioning
confidence: 99%
See 4 more Smart Citations
“…The activated enzyme (factor Xa) is an Arg-specific serine protease related to trypsin, but has much narrower substrate specificity. The N-terminal γ-carboxyglutamic acid (Gla) domain binds B8À10 calcium ions in a cooperative manner (average K d B 0.5 mM) and mediates the interaction of factor X/Xa with phospholipid membranes [4,5,6]. In the presence of calcium ions, factor Xa forms a phospholipid-bound complex with a cofactor, factor Va.…”
Section: Activity and Specificitymentioning
confidence: 99%
“…This 'prothrombinase' complex activates prothrombin (Chapter 643) B300 000fold more rapidly than does free factor Xa. Studies of this reaction have demonstrated that phospholipid reduces the K m for prothrombin, whereas factor Va increases the V max [5]. In vivo, the surface of activated platelets is the main site at which the prothrombinase complex is assembled.…”
Section: Activity and Specificitymentioning
confidence: 99%
See 3 more Smart Citations